2009
DOI: 10.1080/03069880903161393
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between adolescents’ preferred sources of help and emotional distress, ambivalence over emotional expression, and causal attribution of symptoms: a Singapore study

Abstract: Past research has shown that many adolescents with depression and anxiety disorders do not consult mental health professionals. This study examines how emotional distress, ambivalence over emotional expression, and causal attribution of depressive and anxious symptoms are related to adolescents' preferred sources of help for these symptoms. 300 secondary school students in Singapore were surveyed. Results show that distress, ambivalence, psychosocial causation, and biomedical causation were positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“… 19 These beliefs could be related to some youths’ preference for seeking help from Traditional Chinese Medicine physicians. 20 Although participants in these studies also showed beliefs in psychological causes of mental illness and preference for seeking help from mental health professionals, the findings suggest that one’s cultural background may influence one’s views of mental illness. However, stigma and social distance have not been well studied among youths in Singapore.…”
Section: Introductionmentioning
confidence: 85%
“… 19 These beliefs could be related to some youths’ preference for seeking help from Traditional Chinese Medicine physicians. 20 Although participants in these studies also showed beliefs in psychological causes of mental illness and preference for seeking help from mental health professionals, the findings suggest that one’s cultural background may influence one’s views of mental illness. However, stigma and social distance have not been well studied among youths in Singapore.…”
Section: Introductionmentioning
confidence: 85%
“…The researcher found two psychological (humanistic and cognitive-behavioural), one physiological (including Asian physiological explanations) and two supernatural (karmaic, Asian religious beliefs and classical religious beliefs) factors. Another study of local youths showed that belief in physiological causation was associated with preference for Traditional Chinese Medicine physicians and medical doctors, while belief in psychosocial causes was associated with preference for mental health professionals (Lee, 2008). While these two local studies revealed some of the causal beliefs of mental illness, a significant proportion of the Singaporean population, including adults, Malays and Indians are underrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…Ambivalence is characterized in the psychological literature as “overlapping approach-avoidance tendencies, manifested behaviorally, cognitively, or affectively, and directed toward a given person, experience, or other object, as well as toward a set of objects” (Sincoff, 1990, p. 44). Studies have indeed pointed to ambivalence as being linked to low motivation to seek help (e.g., Lee, 2009).…”
mentioning
confidence: 99%